Regular orthoscalar representations of extended dynkin graphs $\widetilde{E}_6$ and $\widetilde{E}_7$ and *-algebras associatedwith them - Livins'kyi, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain a classification of indecomposable orthoscalar representations of the extended Dynkin graphs $\widetilde{E}_6$ and $\widetilde{E}_7$ with a special character and of the *-algebras associated with them, up to the unitary equivalence.